Analisis Peran Pemuda dalam Pengembangan Koperasi di Kota Kisaran - Mr Supandi (Quantitative Economics Journal, 2018)
The objective of the research was to find out the development of cooperatives in Kisaran. The population was all youngsters who lived in Kisaran. The samples were 96 managers of cooperatives that were not youth and dwelled in two subdistricts: Kisaran Barat Subdistrict and Kisaran Timur Subdistrict according to Franck Lynch formula. The data were analyzed by using descriptive percentage analysis in order to find out the role of youth in the development of cooperatives in Kisaran and Shift Share method in order to find out the role of cooperatives in the development of Kisaran. The primary data were gathered by using questionnaires and secondary data were obtained from the related agencies such as the Cooperative, Industry, and Commerce Agency of Kisaran and Central Bureau of Statistics of Kisaran. The result of the descriptive percentage analysis shows as the Agent of Change, they are obliged to improve cooperatives and it is the thing which is done by youth(64.58%). As the Agent of Development, they play an active role in development of cooperatives (68.75%). As the Agent of Modernization, they productively active in marketing cooperatives (68.75%). Therefore, the role of youth influences the development of cooperatives in Kisaran. The result of Shift Share has Proportional shift (P) of 69.76877 which indicates that sub-sector of cooperatives in Asahan Regency has quicker growth than that in the sectors of industry, electricity, gas and drinking water, transportation and communication, and the other services in Kisaran and has Differential Shift (D) of 77.18951 which indicates that sub-sector of cooperatives in Asahan Regency has relatively higher competitiveness than that of the other sectors.